Improving Students’ Writing Skill through Blended Learning during Covid-19 Pandemic - Yanuarti Apsari; Aseptiana Parmawati (Jurnal Pendidikan Edutama, 2022)
Writing is regarded as the most difficult skill for students. Improving students’ writing skill can be done in many ways, including applying online learning platform during covid-19 pandemic. This research aims to describe the implementation of blended learning to improve students’ writing skill and to describe whether blended learning can improve the students’ writing skill or not.  This research employed Collaborative Classroom Action Research. It was conducted into two cycles. The subjecst of the research are a second-year students of IKIP Siliwangi, who enrolled English for Academic Writing class. The research data were collected by using techniques of observation and test. The results of this study show that after the implementation of blended Learning in every cycle, the students’ writing score were getting better. It can be seen from the result of students’ mean score in Cycle 1 was 74  and Cycle  2  was  84.  This means that the implementation of Blended Learning can improve students’ writing skill. In addition, blended learning also can enhance students’ interest in writing